Pembentukan Perumda Pasar Guna Mendorong Perekonomian Daerah - Fachruzzaman Fachruzzaman; Eddy Suranta; Danang Adi Putra; Herawansyah Herawansyah; Indah Oktari Wijayanti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The existence of markets plays a very important role in the economy, both at the local and national levels. Markets are not only places where sellers and buyers meet to carry out transactions, but are also centers of economic activity that influence various aspects of people's lives. Through markets, various goods and services can be bought and sold, thereby meeting people's needs and improving their quality of life. Markets also play a crucial role in determining the prices of goods and services through supply and demand mechanisms. Prices formed in the market reflect the balance between the quantity of goods available and the quantity of goods needed by consumers. This process ensures that resources are allocated efficiently and that the goods most needed by society are available at reasonable prices. It is hoped that the establishment of a Regional Public Company (Perumda) will encourage improvements in the economic sector through various strategic methods and have a broad impact. Perumda can act as a driving force for the local economy by creating new jobs, increasing regional income, and expanding the local economic base. With the operation of Perumda, various economic sectors such as trade, industry and services can develop more rapidly.